(Unintended) Consequences of export restrictions on medical goods during the Covid-19 pandemic. (20th December 2021) - Grassia, Marco; Mangioni, Giuseppe; Schiavo, Stefano; Traverso, Silvio
Abstract: The outbreak of the Covid-19 pandemic led several governments to impose restrictions on the export of medical supplies. Despite being at odds with the canonical prescriptions of the economic theory, non-cooperative measures of this kind remain popular tools in times of crisis. By modelling the diffusion of the effects of export restrictions on the domestic availability of medical goods through the international trade network, we study the zero-sum game logic that lies behind these policies. We show that, even if one abstracts from the complex and non-linear real-world dynamics that characterize global crises, unilateral trade restrictions are not helpful. In fact, while restrictions would be beneficial to a country implementing them in isolation, we observe that their generalized use makes most countries worse off relative to a no-ban scenario. Moreover, the results also indicates restraining from export bans has negligible costs even when other countries apply them. In terms of normative analysis, our results provide new evidence against unilateral trade policies which go above and beyond the context of the current pandemic.